2004
DOI: 10.1097/00004872-200409000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of insulin resistance by troglitazone ameliorates cardiac sympathetic nervous dysfunction in patients with essential hypertension

Abstract: Troglitazone had a beneficial effect on cardiac sympathetic nervous function through a decrease in insulin resistance in patients with essential hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Studies in both animal models of hypertension and in humans with insulin resistance suggest that treatment with thiazolidinediones reduces urinary catecholamines, skin sympathetic nerve activity, and cardiac sympathetic nervous system function (55,59,61). The contribution of sympathetic activation to SLE hypertension has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in both animal models of hypertension and in humans with insulin resistance suggest that treatment with thiazolidinediones reduces urinary catecholamines, skin sympathetic nerve activity, and cardiac sympathetic nervous system function (55,59,61). The contribution of sympathetic activation to SLE hypertension has not been previously examined.…”
Section: Discussionmentioning
confidence: 99%
“…Heart-rate variability studies suggest that insulin resistance may be responsible for early derangements of cardiac autonomic tone, characterized by increased low-to high-frequency ratio or sympathovagal balance, independent of obesity [ 32 ]. Six months of treatment with an insulin-sensitizing agent belonging to the thiazolidinedione group exerted signifi cant cardiac sympathoinhibitory effects by reducing the uptake of norepinephrine from cardiac nerve terminals and increasing its myocardial tissue clearance [ 33 ].…”
Section: Hyperinsulinemia/insulin Resistancementioning
confidence: 99%
“…In the study from Yosefy et al [117] the observed reductions in office BP and plasma insulin in the rosiglitazone group were accompanied with a significant decline in sympathetic skin activity, measured as sympathetic skin potentials by computerised electromyography device, whereas in the glibenclamide group, apart from SBP and plasma insulin elevation an augmentation of skin sympathetic activity was documented. Finally, in the mentioned above study of Watanabe et al [84], along with clinic BP reduction, cardiac sympathetic nervous dysfunction (evaluated using the heartto-mediastinum ratio and mean washout rate measured by 123I-meta-iodobenzylguanidine (MIBG) cardiac imaging) was significantly improved in the troglitazone group, and these changes were significantly correlated with the observed change in IR.…”
Section: Ii) Studies On Sympathetic Nervous System Activitymentioning
confidence: 84%
“…The only study reporting an effect of troglitazone on BP since then is a recently published one, in which 34 patients with mild essential hypertension were treated for 6 months either with antihypertensive drugs or with antihypertensive drugs plus 400 mg of troglitazone [84]. In the troglitazone-treated group clinic BP presented a significant fall of 7.4±5.9/4.8±4.7, whereas in the other group BP remained practically unchanged.…”
Section: Studies With Troglitazonementioning
confidence: 99%